Enhancement of vegetative growth, flowering, yield and fruit quality of 'Hollywood' plum by using biostimulants and foliar fertilizers - Eissa, Fawzia M. (2007)
The response of 'Hollywood' plum (Prunus domestica L.) to treatment with five locally available commercial biostimulants and foliar fertilizers was studied in a private farm in Menofia Governorate, Egypt during the 2005 and 2006 seasons. A randomized complete block design was used. Data were recorded on soil microbial count (viz., bacteria, actinomycetes, and fungi), soil and leaf NPK analysis, foliage characters (viZ., number of leaves, leaf area. and leaf chlorophyll content), flowering. fruit set percentage, yield/tree. and fruit quality attributes (viZ.. fruit weight, size, poiar and equatorial diameters, firmness, flesh thickness, total soluble solids and titratable acidity). Biostimulants applied were Wesko plus K, Which contains 56 % K-humate, micronutrients. polymers and 3 % amino acids; Atonic. which contains 0.6 % aromatic nitrocompounds; Setter·2, which is rich in ascorbic and citric acids, N, Ca, Cu, Mn and B; Faster, which is also rich in ascorbic and citric acids in addition to P and K and contain several organic compounds, including free proteins and peptldes; and Calcuzn, which is rich in N. Ca, Mg and all micronutrients. Most of these biostimulants induced significant positive effects on all measured characters relative to control. The Wesko Plus K treatment ranked first, followed by the Calcuzn treatment; but in several instances, it was not significantly different from the Wesko Plus K treatment. Atonic, Setter-2, and Faster were mostly intermediate in their effects, but one or more of them were, in some of measured characters, not significantly different from the control treatment. It was recommended to use either of the Wesko Plus K or the Calcuzn treatment for improving growth, yield, and fruit quality of 'Hollywood' piums grown under loamy clay soil condition.
Includes reference.
Summary in Arabic.
1
Keywords: Plum -- Fertilization; Plum -- Yields; Plum -- Quality; Plum -- Flowering; Foliar feeding